Mathematical aspects of the Heisenberg uncertainty principle within local fractional Fourier analysis - Yang, Xiao-Jun (2014)
In this paper, we discuss the mathematical aspects of the Heisenberg uncertainty principle within local fractional Fourier analysis. The Schrödinger equation and Heisenberg uncertainty principles are structured within local fractional operators.